Acute Kidney Injury in Methotrexate treated Leukemia - Bipesh Kumar Shah; Seth, Rachna; Sinha, Aditi; Gupta, Aditya Kumar; Meena, Jagdish Prasad (Journal of BP Koirala Institute of Health Sciences, 2023)
Background: The study was performed to know the incidence of acute kidney injury within 48 hours following High dose Methotrexate administration in children with high-risk B cell Acute Lymphoblastic Leukemia along with its risk factors and toxicities. Most studies have been conducted in adults and have included non-Hodgkin lymphoma along with leukemia. There is a paucity of data regarding the burden of Acute kidney injury with Methotrexate use in the pediatric age group with B cell Acute Lymphoblastic Leukemia. Methods: It was a prospective observational study conducted at the pediatric ward of All India Institute of Medical Sciences, New Delhi between 2019 September to 2021 June. Children between 1 to 18 years with high-risk B lineage Acute Lymphoblastic Leukemia planned for high-dose Methotrexate at 3gm/m² were enrolled. The measurement of serum creatinine was done at baseline, 24 and 42 hours while serum methotrexate at 24 and 42 hours, adverse reactions were assessed till day 14 of methotrexate administration. Results: The incidence of Acute Kidney Injury and severe Acute Kidney Injury (stages 2 and 3) at 42 hours of High dose Methotrexate infusion was 24.3% and 12.8% respectively. Low serum albumin was associated with an increased risk of Acute Kidney Injury (p=0.004). Transaminitis and thrombocytopenia were common toxicities. Conclusions: Acute Kidney Injury is common following High dose Methotrexate administration in B cell Acute Leukemic Leukemia. Low serum albumin level increases renal toxicity following methotrexate infusion. The measures to prevent renal toxicity should be instituted promptly in high-risk groups.